RNA-binding protein hnRNPD induces epithelial-mesenchymal transition in Wilms’ tumor via facilitating MAP4K4 mRNA stability - Gang Li; Man Liao; Haibin Bao; Haolun Xu; Jun Wang; Man Zhang; Can Li; Tian Zheng; Chunlei Yang (Molecular Genetics and Genomics, 2026)

Biocontrol potential of Bacillus velezensis lut-Y1: Antifungal lipopeptides against postharvest fungi Alternaria alternata and Penicillium expansum - Hui-Jun Yuan; Yan-Sen Li; Wen-Jin Ma; Tian-Kun Zhao; Zhen-Dong Wang; Miao-Miao He; Shi-Man Yu; Yan-Ying Xu (Physiological and Molecular Plant Pathology, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Constructing Co-O-P bridging to induce spin state reconfiguration: In situ electro-oxidation of P for industrial-scale alkaline water electrolysis - Miao Ma; Chuan-De Qi; Qiao Xia; Qian-Xi Lv; Xin-Jie Tian; Man-Man Li; Sheng-Jun Xu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2026)

Anomalous intensification of the subtropical East Asian monsoon during Marine Isotope Stage 6.5 - Jianxiong Hu; Enqing Huang; Peijun Qiao; Man Zhao; Guodong Jia; Jun Tian (Quaternary Science Reviews, 2026)

Rationally designed aluminum-supported g-C3N4: An efficient and halogen-free catalyst for CO2-epoxide cycloaddition - Man Zhao; Wen-Jun Xie; Shan-Shan Chen; Hong-Ru Li; Liang-Nian He (Journal of Environmental Chemical Engineering, 2026)

Oxophilic Nb incorporation induces reaction pathway transition in hollow RuO2 toward durable acidic oxygen evolution - Jie Zhang; Man Luo; Jun Liang; Wenyuan Gao; Jingbin Huang; Yibing Li; Xinhui Yang; Jie Zhu (Chemical Engineering Journal, 2026)

Allelic variation in cis-regulation of UNE12 underlies differential Verticillium wilt resistance in tetraploid cottons - Meixia Xie; Ziming Li; Jiaxuan Zhao; Minghui Ye; Mengjia Jiao; Zhicheng Wang; Xinxin Zheng; Xinyu Zhang; Jin Zhang; Yan Wang; Man Gu; Lingxia Zhai; et al. (Science Bulletin, 2026)

Riverine Li isotopes response to a flood event on the Chinese Loess Plateau - Jianqi Man; Long-Fei Gou; Zheng Chen; Wenqi Zhang; Jiayuan Ren; Zhiyuan Zhao; Chengfan Yang; Haoqiang Dong; Chenyuan Kang; Jun Xiao; Zhi-Qi Zhao; Zhenhong Li; et al. (Geochimica et Cosmochimica Acta, 2026)

PD-1/PD-L1 inhibition after cryoablation is associated with improved tumor control and immunosuppressive microenvironment remodeling in Lewis lung adenocarcinoma - Qi Liu; Shuo Zhang; Xuxin Chen; Jiao Li; Man Qi; Yongqun Li; Yiwei Ding; Xiaoyu Zhao; Jun Shi; Jiajia Tang; Meng Liu; Xue Wang; et al. (Cryobiology, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Detection and enrichment of mucin-5 AC from edible bird's Nest - Jun Yin; Juan Nie; Hongyuan Chen; Shang Chen; Man Yuan; Dongliang Wang; Xinke Zhang (Food Chemistry, 2026)

Hydrocarbon ionomer catalyst layer engineering for high-performance all-hydrocarbon-based proton exchange membrane water electrolysis - Jaehun Choi; Hwan Yeop Jeong; Yi Sak Noh; Sang Jun Yoon; Keun-Hwan Oh; Hong Suk Kang; Soonyong So; Duk Man Yu (Chemical Engineering Journal, 2026)

Cell identity uncertainty and exposure heterogeneity in germ cell-resolved comet assays - Man Sun; Dan Zang; Jun Chen (Archives of Toxicology, 2026)

Burdock leaf polysaccharide as a clean-label bio-preservative for meat: Structural characterization, multifaceted antibacterial mechanisms, and shelf-life extension efficacy - Yong-xin Li; Chan Zhang; Linchong Hui; Xiangfeng Liu; Yuting Sun; Man Liu; Jun Tian (Food Chemistry, 2026)

Regional mapping of soil heavy metals via a novel deep learning approach: A case study in the Yangtze River Delta, China - Lei Ju; Bifeng Hu; Mingkai Qu; Jun Man (Journal of Hazardous Materials, 2026)

White peroxidase-mimicking Mn-MOF enabled smartphone-assisted colorimetric sensor for on-site visual detection of perfluorooctane sulfonate in water samples - Shao-Hua Wen; Jun Zhan; Hao Wu; Yule Ji; Qingpeng Zhao; Ziqi Yuan; Junping Ma; Sha Yu; Yuanzhen Zhou; Man Ge (Journal of Environmental Chemical Engineering, 2026)

High-crystallinity CsPbBr3 grown by unseeded accelerated evaporation for stable and ultralow-dose X-ray detection - Jangwon Byun; Ahreum Park; Beomjun Park; Sung-Jun Park; Jichul Seo; Joo-Hong Lee; Wonho Lee; Jin-Wook Lee; Dong Hoe Kim; Man-Jong Lee (Chemical Engineering Journal, 2026)

Optimization of microalgal growth parameters for enhanced biohydrogen production via biophotolysis in Chlorella sp. - Yi Jie Liew; Sie Yon Lau; Murat Yılmaz; Man Kee Lam; Jun Wei Lim (Biotechnology Letters, 2026)
The increasing reliance on fossil fuels for global energy production has intensified greenhouse gas emissions, highlighting the need for sustainable energy alternatives. Hydrogen is considered a promising green fuel due to its high energy density and conversion efficiency. Among various production pathways, microalgae-based biohydrogen generation via biophotolysis is particularly attractive owing to its high biomass productivity, adaptability to diverse water sources, flue gas mitigation potential, and low land requirements.This study investigates the effects of key microalgal growth parameters on biohydrogen production by Chlorella sp. through biophotolysis. The impacts of nitrogen purging during the transition from aerobic to anaerobic conditions, different photoperiod regimes (continuous illumination, continuous darkness, and a light–dark cycle), glucose supplementation (5, 10, and 15 g L⁻ 1 ), and temperature (25, 30, and 35 °C) were systematically evaluated. Microalgal cell density was monitored during hydrogen production to elucidate its relationship with hydrogen yield. Initial experiments were conducted in 10 mL test tubes to identify optimal conditions, which were subsequently applied to scale-up experiments in a 1000 mL jacketed reactor. Nitrogen purging significantly enhanced hydrogen production by removing oxygen and activating hydrogenase, resulting in a peak hydrogen concentration of 11 ppm. Continuous illumination yielded higher hydrogen levels than darkness and light–dark cycling. Glucose addition substantially increased hydrogen production, with the highest yield observed at 15 g L⁻ 1 (30 ppm). An optimal temperature of 30 °C also maximized hydrogen production. Under these conditions, hydrogen production increased as cell density decreased due to metabolic shifts. Scale-up experiments achieved a 405-fold increase in hydrogen yield, demonstrating the scalability potential of the process. These findings emphasize the importance of optimizing algal growth conditions to balance microalgal growth and biohydrogen production for future industrial applications.

Ginsenoside Rh2 promotes cell apoptosis in T-cell acute lymphocytic leukaemia by MAPK and PI3K/AKT signalling pathways - Beibei Geng; Man Zhao; Jun Wang; Tian Zhong; Chaoyan Kang; Zizhen Wang; Xin Ma; Ting Xia (Natural Product Research, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Synthesis of ZIF-8 derived porous carbon via morphology-controlled electrodeposited ZnO thin films for in-plane micro-supercapacitors - Jun-Yan Lin; Ramasamy Velmurugan; Jing-Jie Lin; Zhi-Ting Huang; Man-Ning Lu; Martin Hulman; Chien-Kuo Hsieh; Jeng-Yu Lin (Chemical Engineering Journal, 2026)

Structural evolution-based ancestral sequence reconstruction of medium-chain alcohol dehydrogenase for efficient synthesis of fused-ring chiral alcohols - Jun Wang; Songyin Zhao; Lehang Li; Manman Zhu; Man Zou; Xin Su; Jie Gu; Yan Xu; Yao Nie (Bioresource Technology, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Comparison between genomic alterations in mouse, pig, and human through whole-genome sequencing - Geon Hue Bae; Seong Gyu Kwon; Jeong-Woo Choi; Joo Hee Hong; CheolMin Jeon; Areum Cho; JaeEun Shin; Mee Sook Jun; Man-Hoon Han; Seock Hwan Choi; Ji Won Oh (Journal of Genetics, 2026)

Shape-driven toxicity of polystyrene microplastics: Impacts on physiology and gut microbiota in Daphnia magna - Ve Van Le; Mehwish Taj; Maranda Esterhuizen; Young Jun Kim; Man-Young Jung; Sang-Ah Lee (Marine Pollution Bulletin, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Metabolomics-based authentication of acacia honey against C3 and C4 sugar adulteration - Yumi Kim; Man Young Jo; Hyejeong Jeong; Jun Woo Cho; Hui-Seung Kang; Moon-Ik Chang; Do Yup Lee (Food Chemistry, 2026)

Body size drives male reproductive success through nest competition and paternal care in the toad Leptobrachium boringii - Raziya Abliz; Wei Zhang; Shuang Liu; Rufeng Xiong; Chunhua Huang; Jun Li; Mian Zhao; Zhirong Gu; Man Su; Wei Liu; Hua Wu (Animal Behaviour, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Notes on the Description of Novel Prokaryotic Taxa - Wee Fei Aaron Teo; Juan A. Mondotte; Jia Liu; Hilal Ay; Marcelo Luiz Lima Brandão; Man Cai; Claudia Etchebehere; Wen-Jun Li; Wasu Pathom-aree; Tomoo Sawabe; Taegun Seo (Current Microbiology, 2026)

Fine-grained surface sediment provenance in the Hupo Basin, Eastern Coast of Korea - In Kwon Um; Man Sik Choi; Jang-Jun Bahk; Soo Yeon Han (Geo-Marine Letters, 2026)

Microbial interaction strategies of active bacteria shape carbon priming in intensively managed citrus orchard soils - Man Hu; Yunlong Cai; Zonglin Shi; Tianrui Zhai; Hui Zhang; Lianhao Zhou; Jun Li; Quan Zhou; Quanchao Zeng (Applied Soil Ecology, 2026)

Optimizing electrode-integrated microalgae cultivation systems for simultaneous bioelectricity and lipid production - Amina Lami Mohammed; Man Kee Lam; Uganeeswary Suparmaniam; Jun Wei Lim; Inn Shi Tan; Sie Yon Lau; Bridgid Lai Fui Chin; Peck Loo Kiew (Algal Research, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Corrigendum to ‘Impact of various microalgal-bacterial populations on municipal wastewater bioremediation and its energy feasibility for lipid-based biofuel production’ [J. Environ. Manag., Volume 249 (2019), 109384] - Wai Hong Leong; Siti Nur Azella Zaine; Yeek Chia Ho; Yoshimitsu Uemura; Man Kee Lam; Kuan Shiong Khoo; Worapon Kiatkittipong; Chin Kui Cheng; Pau Loke Show; Jun Wei Lim (Journal of Environmental Management, 2026)

Quantifying climate conditions for the formation of bauxites and kaolinites - Xiujuan Bao; Yongyun Hu; Xiang Li; Jiaqi Guo; Shuai Yuan; Mengyu Wei; Zhibo Li; Kai Man; Zihan Yin; Jing Han; Jian Zhang; Qiang Wei; et al. (Global and Planetary Change, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Enhanced photocatalytic uranium(VI) removal via oxygen vacancy-assisted Z-scheme SPC-Bi/Bi2WO6 with plasmonic Bi activation - Le Tao; Xue-Qi Fan; Yi-Man Sun; Yue Hu; Wen-Yan Guo; De-Qiang Ji; Hong-Jun Wu; De-Bin Ji (Chemical Engineering Journal, 2026)

SLC6A14 as a Key Diagnostic Biomarker for Ulcerative Colitis: An Integrative Bioinformatics and Machine Learning Approach - Xiao-Jun Ren; Man-Ling Zhang; Zhao-Hong Shi; Pei-Pei Zhu (Biochemical Genetics, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Valorizing lentil waste extract into a functional biopolymer for eco-friendly harvesting of Chlorella vulgaris - Shobita Sree Gunasegaran; Hemamalini Rawindran; Yeek Chia Ho; Jun Wei Lim; Man Kee Lam; Azima Syafaini Japar; Wai Hong Leong (Process Safety and Environmental Protection, 2026)

Hop bitter acids from the pistillate flower of Humulus lupulus L. and their anti-inflammatory and anti-dengue virus activities - Biao Sun; Yun-Lin Ao; Xia Cao; Jia-Bing Zhang; Xia Zhang; Dong-Hao Lu; Man Lin; Jun-Shan Liu; Xiao-Qi Zhang (Phytochemistry, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Improving the presentation of HONO in CMAQ based on observations over the Yangtze River Delta Region - Shuxian Zhang; Jie Yao; Honghui Xu; Jun He; Man Yue; Meng Shan; Fan Meng; Xiaoai Jin; Ziqi Jin; Huansang Chen; Yilei Dong (Atmospheric Research, 2026)

Dynamic Characterization of the 2009 Jiweishan Rockslidein Wulong, China, Based on Broadband Seismic Observations - Kai Chen; Meng Zhang; Man-qiu He; Jiang Yi; Tong-jun Wang (Applied Geophysics, 2025)

Determination of dissolved inorganic carbon export and the controlling factors in small mountainous Rivers, Taiwan - Man-Ching Choi; Pei-Hao Chen; Chi-Wang Tsui; Jr-Chuan Huang; Jun-Yi Lee; Li-Chin Lee (Journal of Hydrology, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

The effect and mechanism of sublethal injury by lactic acid on Salmonella Typhimurium planktonic and biofilm cells - Mengjiao Zhang; Yunshuang Man; Rongrong Yang; Yudi Wang; Dongling Yan; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Microbiology, 2025)

OptimDase: An Algorithm for Predicting DNA Binding Sites with Combined Feature Encoding - Zhendong Liu; Jun S. Liu; Dongqing Wei; Rongjun Man; Jiamin Jiang; Bofeng Zhang; Liping Li; Zhiyong Zhao (Interdisciplinary Sciences: Computational Life Sciences, 2025)
Identifying DNA binding sites remains a critical task in bioinformatics, with applications ranging from gene regulation studies to drug design. Although progress has been made in computational techniques, we still face challenges such as data complexity and prediction accuracy. In this paper, we introduce OptimDase, a new algorithm. It integrates feature encoding with optimum decision-making frameworks to improve DNA binding site prediction. OptimDase integrates multi-scale scanning and feature selection strategies, making it highly effective for both classification and regression tasks. Our experiments demonstrate that OptimDase achieves superior performance with an accuracy of 0.8943 in classification tasks and an RMSE of 0.0054 in regression tasks, outperforming existing algorithms in key evaluation metrics. These results highlight OptimDase’s portability and robustness, making it an effective solution for identifying DNA binding sites and advancing the applications of drug design. Graphical Abstract

Optimization and structure-property relationships of poly(lactic acid)/poly(butylene succinate) (PLA/PBS) biocomposites reinforced with biofiller from defatted Chlorella vulgaris - Yaleeni Kanna Dasan; Uganeeswary Suparmaniam; Man Kee Lam; Jun Wei Lim; Yeek Chia Ho; Voon-Loong Wong; Inn Shi Tan; Peck Loo Kiew; Chung Hong Tan; Sieh Kiong Tiong (Algal Research, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Deriving nickel carbides from Ni-MOFs to boost CO selectivity in CO2 hydrogenation - Xiaorui Wang; Guiming Xie; Chaonan Cui; Yi Man; Zhou-jun Wang (Fuel, 2025)

Unraveling urban nighttime aerosol characteristics and meteorological factors on AOD-PM relationships in East Asia - Jing Li; Jiaqi Jin; Man Sing Wong; Jun Wang; Kwon Ho Lee; Kai Qin; P.W. Chan (Atmospheric Environment, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Insights into pollution characteristics of phthalate esters in soil-crop systems and associated responses of soil microbial communities: The case study of Pengzhou, China - Xin Qi; Yu-Hao Zhao; Yu-Bon Man; Ming-Hung Wong; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Gun-Yin Wang; Chang-Lian Xu; Jun-Zhuo Cai; Zhang Cheng (Journal of Environmental Chemical Engineering, 2025)

Intestinal microbiota and metabolomics reveal the intestinal damage caused by imidacloprid in loaches (Misgurnus anguillicaudatus) - Yingbing Su; Yongxi Huang; Pupu Yan; Jiali Liu; Man Liu; Jun Zhu; Yinuo Gong; Haishan Chen; Liwei Guo (Aquatic Toxicology, 2025)

Unraveling Predominantly Inattentive ADHD (ADHD-PI): Insights from Proteomic Analysis of the Striatum of Thyroid Hormone-Responsive Protein (THRSP)–Overexpressing Mice - Raly James Perez Custodio; Leandro Val Sayson; Ara Cho; Hyeryeon Jung; Darlene Mae Ortiz; Hyun Jun Lee; Emad Alyan; Edmund Wascher; Stephan Getzmann; Mikyung Kim; Kyeong‑Man Kim; Eugene C. Yi; et al. (Molecular Neurobiology, 2025)
Attention-deficit/hyperactivity disorder, or ADHD, is a neurodevelopmental disorder with poorly understood molecular mechanisms. Recent studies have proposed that gene expression involved in regulating synaptic transmission in the striatum may play a role in ADHD pathogenesis. To explore the molecular basis of ADHD, we utilized proteomic analysis using whole striatal tissues from early adult thyroid hormone-responsive protein-overexpressing (THRSP-OE) mice, which displayed defining characteristics of predominantly inattentive ADHD (ADHD-PI). We focused on the striatal brain region due to its critical role in the regulation of attention, motivation, and reward processing. Moreover, the striatum modulates dopaminergic pathways that are known to be impaired in ADHD. Our analysis revealed an innate overexpression of Snap25 protein in THRSP-OE mice, indicating possible alterations in the SNARE protein complex and potential neurotransmitter dysregulation. Furthermore, a binding affinity study showed reduced dopamine D1 receptor binding concentrations and pronounced low dopamine levels in THRSP-OE mice. Repeated seven-day injections of methylphenidate improved the low dopamine levels, reducing the EEG theta/beta ratio in this animal model. These findings suggest new markers specific to the ADHD-PI presentation and further support the role of Snap25 dysregulation and possible SNARE protein complex alterations in ADHD-PI.

Room temperature natural light promoted DMSO/O2-catalyzed N-acylation reaction of imidazoles/triazoles with cyclopropenones - Guo-Dong Shen; Zhi-Rong Zhao; Kun Bi; Yi Man; Jun-Tong Liu; Xian-Qiang Huang; Xin Lv (Molecular Diversity, 2025)

Impact of plant litter decomposition on soil microbial diversity and ecosystem multifunctionality - Quanchao Zeng; Lianhao Zhou; Quan Zhou; Jun Li; Zhe Chen; Man Hu; Wenfeng Tan (Applied Soil Ecology, 2025)

Long-term variations in plankton community structure and environmental drivers in Korean artificial lake - Hye Jeong Choi; Yukyong Cheong; Man-Sig Jun; Moon Sook Kim; Hojeong Yeom Yeom; Seyoon Jung; Yong-Bin An; Yoonseok Kim; Mingyeong Bak; Bomchul Kim; Eun-Mi Hong (Algae, 2025)
With the intensification of global warming, the occurrence of harmful algal blooms (HABs) in freshwater ecosystems have become more prolonged and frequent. As phytoplankton and zooplankton are sensitive to changes in environmental conditions such as temperature, light intensity, and nutrients, understanding how environmental factors affect plankton community structure can help to predict the response of freshwater ecosystems to climate change. However, studies on the long-term monitoring of plankton community structure in Lake Soyang, an important source of drinking water for metropolitan areas in South Korea, and other domestic freshwater systems in Korea remain limited. Here, we investigated the changes in phytoplankton and zooplankton community composition in response to environmental factors in Lake Soyang during a long-term survey period. The results revealed that diatoms were negatively correlated (p

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Temperature dependent evaporite-sourced Li isotopic seasonality in the upper Yellow River - Long-Fei Gou; Jiayuan Ren; Zheng Chen; Jianqi Man; Wenqi Zhang; Zhengjie Chen; Jun Xiao; Zhangdong Jin (Global and Planetary Change, 2025)

Additive-free nitrile-based gel polymer electrolytes with enhanced interfacial compatibility for Lithium metal batteries - Yuxue Sun; Man Wang; Xiaorong Zhang; Haiming Xie; Jun Liu (Chemical Engineering Journal, 2025)

Enhancing lipid yield in freshwater microalgae through synergistic abiotic stressors for sustainable biodiesel production - Uganeeswary Suparmaniam; Cheng Yaw Li; Man Kee Lam; Nurul Tasnim Sahrin; Hemamalini Rawindran; Chin Seng Liew; Jun Wei Lim; Inn Shi Tan; Sie Yon Lau; Bridgid Lai Fui Chin (Biomass and Bioenergy, 2025)

Parametric CFD-FEA Study on the Aerodynamic and Structural Performance of NaviScreen for Wind Resistance Reduction in Medium-Sized Commercial Ships - Jin-Man Kim; Jun-Taek Lim; Kwang Cheol Seo; Joo-Shin Park (Journal of Marine Science and Engineering, 2025)
Meeting the International Maritime Organization’s (IMO) 2050 targets for reducing greenhouse gas (GHG) emissions requires cost-effective solutions that minimize wind resistance without compromising safety, particularly for medium-sized multipurpose vessels (MPVs), which have been underrepresented in prior research. This study numerically evaluates 20 bow-mounted NaviScreen configurations using a coupled high-fidelity computational fluid dynamics (CFD) and finite element analysis (FEA) approach. Key design variables—including contact angle (35–50°), lower-edge height (1.2–2.0 m), and horn position (3.2–5.3 m)—were systematically varied. The sloped Type-15 shield reduced aerodynamic resistance by 17.1% in headwinds and 24.5% at a 30° yaw, lowering total hull resistance by up to 8.9%. Nonlinear FEA under combined dead weight, wind loads, and Korean Register (KR) green-water pressure revealed local buckling risks, which were mitigated by adding carling stiffeners and increasing plate thickness from 6 mm to 8 mm. The reinforced design satisfied KR yield limits, ABS buckling factors (>1.0), and NORSOK displacement criteria (L/100), confirming structural robustness. This dual-framework approach demonstrates the viability of NaviScreens as passive aerodynamic devices that enhance fuel efficiency and reduce GHG emissions, aligning with global efforts to address climate change by targeting not only CO2 but also other harmful emissions (e.g., NOx, SOx) regulated under MARPOL. The study delivers a validated CFD-FEA workflow to optimize performance and safety, offering shipbuilders a scalable solution for MPVs and related vessel classes to meet IMO’s GHG reduction goals.

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Electrochemical degradation of toluene-2,4-diamine by graphene oxide-modified Ti/Sb-SnO2/α-PbO2/β-PbO2 anode: Performance and mechanism - Shuaishuai Man; Jun Zhang; Hebin Bao; Yifan Ge; Youcun Bai; Xinyu Liu; Ziyang Li; Liwei Qiu; Zhenzhen Zhao; Qun Yan (Environmental Research, 2025)

Comprehensive insights into the mechanism of flavor formation in mandarin fish (Siniperca chuatsi) with inoculated fermentation - Ke-Xun Guo; Bin Hu; Yi Jiang; Zeng-Yong Li; Jun Qi; Man-Man Yu (Food Chemistry, 2025)

Cadmium exposure and health outcomes:An umbrella review of meta-analyses - Wenzhuo Xu; Sainan Wang; Wenhua Ruan; Mingyue Hao; Kele Jiang; Hao Guo; Anyi Geng; Mengting Man; Zheng Hu; Yun Liu; Guifang Jin; Haiyan Shi; et al. (Environmental Research, 2025)

A crystalline triazine covalent organic framework with partial fluorination for efficient hydrogen peroxide production toward water treatment - Limin Jin; Man Deng; Jun Gao; Lichao Wang; Qi Zhou; Xiujuan Tang; Qiang Li; Hao Du; Derek Hao; Qi Wang (Chemical Engineering Journal, 2025)

Altitude-induced shifts in bacterial communities involved in soil organic phosphorus cycling on Taibai mountain - Lianhao Zhou; Quan Zhou; Yanan Chen; Quanchao Zeng; Jun Li; Man Hu; Baohong Yu; Ruifeng Chen (CATENA, 2025)

Serotonin 2C receptors are also important in head-twitch responses in male mice - Raly James Perez Custodio; Darlene Mae Ortiz; Hyun Jun Lee; Leandro Val Sayson; Mikyung Kim; Yong Sup Lee; Kyeong-Man Kim; Jae Hoon Cheong; Hee Jin Kim (Psychopharmacology, 2025)

Unveiling the influence of the Afatg3 gene: Autophagy's role in sporulation, aflatoxin synthesis, pathogenicity, and drug stress response in Aspergillus flavus - Yong-xin Li; Yan Ma; Chao Pan; Linchong Hui; Chan Zhang; Man Liu; Kunlong Yang; Xue Peng; Jun Tian (Food Bioscience, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Two new triterpenoids from the stems of Euphorbia royleana - Wen-Xing Liu; Man Zhang; Ying-Jun Zhang; Ping Zhao (Natural Product Research, 2025)

Solasodine binds to glucocorticoid receptor to ameliorate airway remodeling and excessive autophagy in bronchial smooth muscle cells for allergic asthma - Zhen Guo; Jun-li Liu; Yan-ni Fang; Xiao-man Guo; Chun-long Ma; Jing-wei Wang (Toxicology and Applied Pharmacology, 2025)

Identification of Dufulin photolysis and hydrolysis products in water using a 13C stable isotope assisted HPLC-HRMS strategy - Bochi Yu; Yanli Man; Gabriel Sigmund; Pingping Wang; Jun Xie; Wei Wang; Lan Zhang; Liangang Mao; Lizhen Zhu; Chi Wu; Xingang Liu (Water Research, 2025)

The concomitant tumor suspension cells derived from SKBR-3 exhibit circulating tumor cell features - Daiye Li; Feihong Liu; Shanshan Li; Xiaoli Zhao; Kelvin Wai Kwok Yeung; Tak Man Wong; Jun Wu (Tissue and Cell, 2025)

Widely targeted metabolomics analysis reveals dynamic changes in metabolites of 'Hass' avocado during postharvest ripening period - Ying Xin; Na Li; Hong-Tao Zhu; Ya-Zhi Li; Han-Zhang Xiang; Jia-Huan Shang; Man Zhang; Ying-Jun Zhang (Food Chemistry, 2025)

Distribution patterns of nitrous oxide during the summer season in the Prydz Bay, eastern Southern Ocean - Jiexia Zhang; Damian L. Arévalo-Martínez; Liyang Zhan; Liqi Chen; Jun Zhao; Wangwang Ye; Man Wu; Yuhong Li; Jian Liu (Acta Oceanologica Sinica, 2025)

Curdlan inclusion modifies the rheological properties and the helix-coil transition behavior of gelatin and increases the flexibility of gelatin films - Xinyu Sun; Yongxin Liu; Xinyi Li; Liya Chen; Man Li; Qingjie Sun; Fenghuan Wang; Jun Hao; Fengwei Xie; Yanfei Wang (Food Chemistry, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Effect of metal–organic framework on hydrogen volume fraction in the oxygen-rich anode catalyst layer of proton exchange membrane water electrolyzer - Inku Kang; Sojin Lee; Won-Jong Choi; Siyeon Lee; Soonyong So; Duk Man Yu; Sang Jun Yoon; Dong-Won Kim; Kwan Woo Nam; Keun-Hwan Oh (Chemical Engineering Journal, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Correlation between the structures of natural polysaccharides and their properties in regulating gut microbiota: Current understanding and beyond - Wing-Shan Keung; Wei-Hao Zhang; Han-Yan Luo; Kam-Chun Chan; Yui-Man Chan; Jun Xu (Carbohydrate Polymers, 2025)

Entropy-informed multi-stage sampling design for soil pollution mapping in heavy metal contaminated areas - Lei Ju; Jiaying Chen; Guifang Liu; Jun Man; Jiajing Chen (Environmental Pollution, 2025)

Insights into selectivity modulation for CO2 hydrogenation over Na-NiLa(BDC) catalysts: The role of frustrated Lewis pairs - Xiaorui Wang; Yi Man; Runduo Zhang; Chaonan Cui; Kangzhou Wang; Zhou-jun Wang (Chemical Engineering Journal, 2025)

Multiscale modelling and infection probability of SARS-CoV-2 transmission in a typical lecture theatre - Mei Yan Chong; Hui An; Peng Cheng Wang; Chew Beng Soh; Szu-Cheng Chien; Edward Reuben Roch; Jun Jie Koh; Simon Ching Man Yu (Building and Environment, 2025)

Uncovering the mechanisms of diosmin in treating obesity-related kidney injury based on network pharmacology, molecular docking, and in vitro validation - Jun-Xing Zhu; Fan Chu; Wen-Man Zhao; Rui Shi; Zhi-Juan Wang; Xun-Liang Li; Yu-Yu Zhu; De-Guang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Inactivation and sublethal injury of Salmonella Typhimurium on beef and in aqueous solution treated with lactic acid - Yunshuang Man; Mengjiao Zhang; Hui Tang; Rui Wen; Rongrong Yang; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Research International, 2025)

Heat stress induces a three-phase thermoregulatory response in different hot and humid environments in rats - Lei Li; Jikuai Chen; Juelin Chen; Yawei Wang; Yankun Pei; Man Wang; Wenjun Chang; Jun Ma; Qing Song; Shuogui Xu (Science of The Total Environment, 2024)

Numerical modeling of double-ring infiltrometers for determining saturated hydraulic conductivity of heterogeneous and anisotropic soils - Xiaoting XIE; Hongxiang ZHOU; Laosheng WU; Jun MAN (Pedosphere, 2024)

Comparison of primary and secondary metabolites and antioxidant activities by solid-state fermentation of Apios americana Medikus with different fungi - Hee Yul Lee; Hyo Seon Kim; Min Ju Kim; Young Hye Seo; Du Yong Cho; Ji Ho Lee; Ga Young Lee; Jong Bin Jeong; Mu Yeun Jang; Jin Hwan Lee; Jun Lee; Kye Man Cho (Food Chemistry, 2024)

Methylparaben changes the community composition, structure, and assembly processes of free-living bacteria, phytoplankton, and zooplankton - Man Wang; Shengxing Wang; Huabing Li; Zhendu Mao; Yiwei Lu; Yunshan Cheng; Xiaotong Han; Yujing Wang; Yanru Liu; Shiqiang Wan; Li-Jun Zhou; Qinglong L. Wu (Environmental Research, 2024)

Comprehensive analysis of somatic mutations and structural variations in domestic pig - Seong Gyu Kwon; Geon Hue Bae; Joo Hee Hong; Jeong-Woo Choi; June Hyug Choi; Nam Seop Lim; CheolMin Jeon; Nanda Maya Mali; Mee Sook Jun; JaeEun Shin; JinSoo Kim; Eun-Seok Cho; et al. (Mammalian Genome, 2024)

Corrigendum to “Association of urban green space with metabolic syndrome and the role of air pollution” [Landsc. Urban Plann. 248 (2024) 105100] - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Excitotoxic Storms of Ischemic Stroke: A Non-neuronal Perspective - Xiao-man Yang; Hao Yu; Jia-xin Li; Na Li; Chong Li; Dong-han Xu; Hao Zhang; Tian-he Fang; Shi-jun Wang; Pei-yu Yan; Bing-bing Han (Molecular Neurobiology, 2024)

The changes in HMOs of GDM mothers over lactation: Regulation on the gut microbiota development in offspring - Lina Zhang; Jinyue Zhang; Yalu Yan; Sufang Duan; Xuemin Wang; Ignatius Man-Yau Szeto; Jun Liu; Zhaona Sun; Xiang Feng; Kasper Hettinga; Peng Zhou (Food Bioscience, 2024)

Optically manipulated nitrate-salt-based direct absorption solar collectors for a photothermal energy harvesting system - Chun-Man Kan; Sih-Wei Chang; Jun-Yi Li; Juan Carlos Cisneros; Hsuen-Li Chen (Chemical Engineering Journal, 2024)

Impact of Dietary Cadmium Intake from Rice on Renal Function Biomarker and Population Toxicokinetic Modelling - Yi Gu; Jun Man; Liqin Su; Shengnan Zhang; Fang-Jie Zhao; Yijun Yao; Peng Wang (Exposure and Health, 2024)

Multiporous PMMA microballs as a novel fluorescence tissue marker - Hyoung-Jun Kim; Seon Sook Lee; Dae Kyung Sohn; Hong Man Yoon; Kyong-Lin Park; Sung-Jae Park; Yongdoo Choi (Chemical Engineering Journal, 2024)

Association of urban green space with metabolic syndrome and the role of air pollution - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Serum LDL Promotes Microglial Activation and Exacerbates Demyelinating Injury in Neuromyelitis Optica Spectrum Disorder - Man Chen; Yun-Hui Chu; Wen-Xiang Yu; Yun-Fan You; Yue Tang; Xiao-Wei Pang; Hang Zhang; Ke Shang; Gang Deng; Luo-Qi Zhou; Sheng Yang; Wei Wang; et al. (Neuroscience Bulletin, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory demyelinating disease of the central nervous system (CNS) accompanied by blood-brain barrier (BBB) disruption. Dysfunction in microglial lipid metabolism is believed to be closely associated with the neuropathology of NMOSD. However, there is limited evidence on the functional relevance of circulating lipids in CNS demyelination, cellular metabolism, and microglial function. Here, we found that serum low-density lipoprotein (LDL) was positively correlated with markers of neurological damage in NMOSD patients. In addition, we demonstrated in a mouse model of NMOSD that LDL penetrates the CNS through the leaky BBB, directly activating microglia. This activation leads to excessive phagocytosis of myelin debris, inhibition of lipid metabolism, and increased glycolysis, ultimately exacerbating myelin damage. We also found that therapeutic interventions aimed at reducing circulating LDL effectively reversed the lipid metabolic dysfunction in microglia and mitigated the demyelinating injury in NMOSD. These findings shed light on the molecular and cellular mechanisms underlying the positive correlation between serum LDL and neurological damage, highlighting the potential therapeutic target for lowering circulating lipids to alleviate the acute demyelinating injury in NMOSD.

Rederiving kinetics to model biohydrogen production from immobilized microalgae alginate beads at various polymerization degrees of alginate under dark fermentative environment - Jia Min Woon; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Jun Wei Lim; Woei-Yenn Tong; Yi Jing Chan; Chuxia Lin; Pei Sean Goh; Sabah Ansar; Man Kee Lam (Algal Research, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Comparative analysis of LC-MS/MS and real-time PCR assays for efficient detection of potential allergenic silkworm - Seung-Man Suh; Kyungdo Kim; Seung-Min Yang; Hana Lee; Minkyung Jun; Jisun Byun; Hyeongjoo Lee; Daseul Kim; Dain Lee; Jae-Eun Cha; Jun-Su Kim; Eiseul Kim; et al. (Food Chemistry, 2024)

Nitric oxide-mediated regulation of Aspergillus flavus asexual development by targeting TCA cycle and mitochondrial function - Kunlong Yang; Yue Luo; Tongzheng Sun; Han Qiu; Qingru Geng; Yongxin Li; Man Liu; Nancy P. Keller; Fengqin Song; Jun Tian (Journal of Hazardous Materials, 2024)

Mechanical behaviour and spatial fracture characteristics of weakly filled granite with different diameters under uniaxial loading revealed by 3D DIC and AE monitoring - Liyun Yang; Fei Zhang; Junxiong You; Donghui Man; Jun Gao; Wei Liu (Bulletin of Engineering Geology and the Environment, 2024)

Enhancing high-density microalgae cultivation via exogenous supplementation of biostimulant derived from onion peel waste for sustainable biodiesel production - Uganeeswary Suparmaniam; Man Kee Lam; Jun Wei Lim; Hemamalini Rawindran; Yeek Chia Ho; Inn Shi Tan; Jibrail Kansedo; Steven Lim; Yoke Wang Cheng; Salman Raza Naqvi (Journal of Environmental Management, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

Imbalance of sediment transport in a meso-tidal bay: effect of tidal pumping and residual circulation - Su In Kim; Jun Young Seo; Jae-Hun Park; Pyeong Joong Kim; In Gwon Kim; Kyung Man Kim; Ho Kyung Ha (Frontiers in Marine Science, 2024)
In-situ mooring systems with acoustic Doppler current profilers were installed in the western (TM01) and eastern (TM02) parts of Yeosu Bay from September 3 to October 2, 2021, to understand the controlling mechanisms of suspended sediment transport. In the bay, freshwater from the Seomjin River freely exchanges with seawater from the open sea. Over the mooring period, current flows were mainly dominated by ebb tides. Power spectral density analysis of the suspended sediment concentration (SSC) exhibited a quarter-diurnal (6.21 h) frequency at TM01 and a semi-diurnal (12.42 h) frequency at TM02. The results suggested that SSC variations in the western part were driven primarily by local sediment resuspension, while they were influenced predominantly by horizontal advection in the eastern part. Differences in SSC variation at the two stations could be due to the physical properties of the bed sediments (TM01: sandy mud containing shell fragments, TM02: mud). Such current flows and SSC variations over the tidal cycles caused an imbalance of sediment transport. At TM01, the sediment fluxes were dominantly seaward due to tidal pumping (88% of the total) and the discharge of suspended sediments in the surface layer by residual circulation. At TM02, landward sediment fluxes were driven primarily by the residual current (73% of the total). Although the suspended sediment fluxes tended to be compensated and balanced mutually by circulation over the entire period, the suspended sediment fluxes at TM02 were approximately twice higher than those at TM01. This was caused by the difference in SSC asymmetry between flood and ebb at the two stations. The mechanisms controlling the transport of suspended sediment could vary spatially, and the relative contribution of tidal pumping and residual circulation could result in an imbalance of sediment transport.

Investigation into the characteristics of bagasse processed with 3C-DES and the production of chemimechanical pulp for pulp molded - Yikui Zhu; Long Li; Yansu Hou; Chuan Xu; Guoxiang Hu; Yi Man; Vasilevich Sergey Vladimirovich; Jun Li; Qingang Xiong (Journal of Cleaner Production, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Human health risk assessment based on a total diet study of daily mercury intake in Chengdu, China - Jun Bo Liu; Ya Jun Zhou; Fang Zhou Du; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Geochemistry and Health, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Long-term evaluation of palm oil mill effluent (POME) steam reforming over lanthanum-based perovskite oxides - Yoke Wang Cheng; Chi Cheng Chong; Chin Kui Cheng; Chi-Hwa Wang; Kim Hoong Ng; Thongthai Witoon; Man Kee Lam; Jun Wei Lim (Journal of Environmental Management, 2024)

Tryptophan sulfonate: A new chemical marker for accurate and efficient inspection of sulfur-treated food products - Kam-Chun Chan; Wei-Hao Zhang; Yui-Man Chan; Hiu-Lam Li; Jing Fang; Han-Yan Luo; Jun Xu (Food Chemistry, 2024)

Construction of robust silica-hybridized cellulose aerogels integrating passive radiative cooling and thermal insulation for year-round building energy saving - Yanmei Liu; Xiaohai Bu; Runqi Liu; Mingxin Feng; Zewu Zhang; Man He; Jun Huang; Yuming Zhou (Chemical Engineering Journal, 2024)

Piperlongumine inhibits esophageal squamous cell carcinoma in vitro and in vivo by triggering NRF2/ROS/TXNIP/NLRP3-dependent pyroptosis - Yue Cui; Xiao-bo Chen; Ying Liu; Qian Wang; Jie Tang; Man-jun Chen (Chemico-Biological Interactions, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

High-performance Al-doped Cu/ZnO catalysts for CO2 hydrogenation to methanol: MIL-53(Al) source-enabled oxygen vacancy engineering and related promoting mechanisms - Guiming Xie; Xingyang Bai; Yi Man; Pengju Ren; Rongrong Jin; Runduo Zhang; Kostya (Ken) Ostrikov; Zhou-jun Wang; Qingyuan Yang (Chemical Engineering Journal, 2024)

Biochar reduces uptake and accumulation of polycyclic aromatic hydrocarbons (PAHs) in winter wheat on a PAH-contaminated soil - Jinfeng WANG; Huanyu BAO; Yu Bon MAN; Jun CAI; Jia LI; Benhua SUN; Fuyong WU (Pedosphere, 2023)

Effect of LuxS/AI-2-mediated quorum sensing system on bacteriocin production of Lactobacillus plantarum NMD-17 - Li-Li Man; Dian-Jun Xiang (Folia Microbiologica, 2023)

Energy balance and life cycle assessments in producing microalgae biodiesel via a continuous microalgal-bacterial photobioreactor loaded with wastewater - Wai Hong Leong; Jun Wei Lim; Hemamalini Rawindran; Chin Seng Liew; Man Kee Lam; Yeek Chia Ho; Kuan Shiong Khoo; Katsuki Kusakabe; Heba Taha M. Abdelghani; Chii-Dong Ho; Hui-Suan Ng; Anwar Usman; et al. (Chemosphere, 2023)

A robust and flexible satellite aerosol retrieval algorithm for multi-angle polarimetric measurements with physics-informed deep learning method - Minghui Tao; Jinxi Chen; Xiaoguang Xu; Wenjing Man; Lina Xu; Lunche Wang; Yi Wang; Jun Wang; Meng Fan; Muhammad Imran Shahzad; Liangfu Chen (Remote Sensing of Environment, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Benthic sediment disturbances by episodic human-controlled discharge in an altered estuary - Seong Woon Jeong; Hun Jun Ha; Kyung Man Kim; Ho Kyung Ha (Marine Geology, 2023)

Empirical estimation of size-resolved scavenging coefficients derived from in-situ measurements at background sites in Korea during 2013–2020 - Yongjoo Choi; Chang Hoon Jung; Junyoung Ahn; Seung-Myung Park; Kyung Man Han; Jongbyeok Jun; Giyeol Lee; Jiyoung Kim; Yongjae Lim; Kyeong-Sik Kang; Ilkwon Nam; Sumin Kim (Atmospheric Research, 2023)

Advancements of microalgal upstream technologies: Bioengineering and application aspects in the paradigm of circular bioeconomy - Wai Hong Leong; Hemamalini Rawindran; Fuad Ameen; Mohammad Mahtab Alam; Yee Ho Chai; Yeek Chia Ho; Man Kee Lam; Jun Wei Lim; Woei-Yenn Tong; Mohammed J.K. Bashir; Balasubramani Ravindran; Nizar Abdallah Alsufi (Chemosphere, 2023)

Kinetic model derived from machine learning for accurate prediction of microalgal hydrogen production via conversion from low thermally pre-treated palm kernel expeller waste - Mohamad Zulfadhli Ahmad Sobri; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sabah Ansar; Md Sohrab Hossain; Worapon Kiatkittipong; Chuxia Lin; Hui-Suan Ng; Juliana Zaini; Muhammad Roil Bilad; Man Kee Lam; et al. (Chemosphere, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Natural polysaccharides protect against diet-induced obesity by improving lipid metabolism and regulating the immune system - Chao Tang; Yuxin Wang; Dan Chen; Man Zhang; Jingguo Xu; Chen Xu; Jun Liu; Juan Kan; Changhai Jin (Food Research International, 2023)

Cyclic dipeptides and alkaloids from the rare actinobacteria Streptacidiphilus carbonis isolated from Sphaerophorus globosus (Huds.) Vain. - Man Hyung Koo; Eun Jae Kim; Jun Hyuck Lee; Se Jong Han; Yung Mi Lee; Seulah Lee; Ui Joung Youn (Biochemical Systematics and Ecology, 2023)

Magma process of the ore-forming gabbrodiorite porphyry of the Meishan iron deposit, eastern China: Insights from the phenocrysts chemistry - Wen-Hao Liu; Man-Rong Jiang; Yan Xia; Xiao-Jun Zhang (Journal of Geochemical Exploration, 2023)

Fundamental alteration of cellular biochemicals from attached microalgae onto palm kernel expeller waste upon optimizing the growth environment in forming adhesion complex - Hemamalini Rawindran; Kuan Shiong Khoo; Baranitharan Ethiraj; Uganeeswary Suparmaniam; Wai Hong Leong; Ratchaprapa Raksasat; Chin Seng Liew; Nurul Tasnim Sahrin; Man Kee Lam; Worapon Kiatkittipong; Jun Wei Lim; Zakariyya Uba Zango; et al. (Environmental Research, 2023)

Baicalin promotes antiviral IFNs production and alleviates type I IFN-induced neutrophil inflammation - Li Li; Jia-Min Dong; He-He Ye; Man-Jing Jiang; Huan-Hua Yang; Lin-Pan Liang; Li-Jun Ning; Ying Wu (Journal of Natural Medicines, 2023)

Numerical simulation on the impact characteristics between rockfalls of different shapes and gravel cushions - Chun Zhu; Jia-jun Xu; Ya-jun Wang; Man-chao He; Sheng-hua Cui; Xiao-hu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Reviewing biohydrogen production from microalgal cells through fundamental mechanisms, enzymes and factors that engendering new challenges and prospects - Jia Min Woon; Kuan Shiong Khoo; Mehdi Akermi; Meznah M. Alanazi; Jun Wei Lim; Yi Jing Chan; Pei Sean Goh; Boredi Silas Chidi; Man Kee Lam; Juliana Zaini; Muhammad Roil Bilad; Yuguang Zhou; et al. (Fuel, 2023)

Liver fibrosis in fish research: From an immunological perspective - Quanquan Cao; Hongying Shan; Ju Zhao; Jinhe Deng; Man Xu; Hao Kang; Tong Li; Ye Zhao; Haifeng Liu; Jun Jiang (Fish & Shellfish Immunology, 2023)

Oxytetracycline-induced oxidative liver damage by disturbed mitochondrial dynamics and impaired enzyme antioxidants in largemouth bass (Micropterus salmoides) - Tong Li; Min Jin; Lishi Huang; Yupeng Zhang; Jiali Zong; Hongying Shan; Hao Kang; Man Xu; Haifeng Liu; Ye Zhao; Quanquan Cao; Jun Jiang (Aquatic Toxicology, 2023)

Influence of environmental stress on microalgae growth and lipid profile: a systematic review - Uganeeswary Suparmaniam; Man Kee Lam; Jun Wei Lim; Suzana Yusup; Inn Shi Tan; Sie Yon Lau; Pravin Kodgire; Surendra Singh Kachhwaha (Phytochemistry Reviews, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Spatio-temporal accumulation and sources of anthropogenic Pb in Ulleung Basin sediments, East/Japan Sea, based on stable Pb isotope ratios - Jun-Sik Woo; Man-sik Choi; Yun-ho Song (Environmental Science and Pollution Research, 2023)

Argonaute-triggered visual and rebuilding-free foodborne pathogenic bacteria detection - Yaru Li; Jun Kou; Xiao Han; Jiali Qiao; Wenlu Zhang; Shuli Man; Long Ma (Journal of Hazardous Materials, 2023)

Structural characterization and stability of glycated bovine serum albumin-kaempferol nanocomplexes - Run-Hui Ma; Wei Wang; Cai-Ping Hou; Yi-Fei Man; Zhi-Jing Ni; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2023)

Unlocking the potential of microalgae bio-factories for carbon dioxide mitigation: A comprehensive exploration of recent advances, key challenges, and energy-economic insights - Yaleeni Kanna Dasan; Man Kee Lam; Yee Ho Chai; Jun Wei Lim; Yeek Chia Ho; Inn Shi Tan; Sie Yon Lau; Pau Loke Show; Keat Teong Lee (Bioresource Technology, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Research progress on postharvest sweet potato spoilage fungi Ceratocystis fimbriata and control measures - Man Liu; Qianchu Meng; Sen Wang; Kunlong Yang; Jun Tian (Food Bioscience, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Unexpected enrichment of antibiotic resistance genes and organic remediation genes in high-altitude lakes at Eastern Tibetan Plateau - Yiwei Lu; Man Wang; Chunyan Yu; Qiong Wu; Zhendu Mao; Huabing Li; Lijuan Ren; Jin Zeng; Peng Xing; Li-Jun Zhou; Shiqiang Wan; Qinglong L. Wu (Science of The Total Environment, 2023)

Effects of dietary supplementation with saccharicterpenin alleviates diarrhea of piglets - Man Wang; Bing Yu; Jun He; Jie Yu; Yuheng Luo; Junqiu Luo; Xiangbing Mao; Daiwen Chen (Livestock Science, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Inhibitory effect of cinnamaldehyde on Fusarium solani and its application in postharvest preservation of sweet potato - Chao Pan; Kunlong Yang; Famous Erhunmwunsee; Yong-Xin Li; Man Liu; Shenyuan Pan; Dongjing Yang; Guoquan Lu; Daifu Ma; Jun Tian (Food Chemistry, 2023)

Cardiac sapogenins from Periploca forrestii - Jun Jin; Man Meng; Jun-you Jian; Wei Gu; Chun-mao Yuan; Xiao-jiang Hao; Lie-jun Huang (Phytochemistry Letters, 2023)

Methcathinone Increases Visually-evoked Neuronal Activity and Enhances Sensory Processing Efficiency in Mice - Jun Zhou; Wen Deng; Chen Chen; Junya Kang; Xiaodan Yang; Zhaojuan Dou; Jiancheng Wu; Quancong Li; Man Jiang; Man Liang; Yunyun Han (Neuroscience Bulletin, 2023)

Specific activation of cGAS-STING pathway by nanotherapeutics-mediated ferroptosis evoked endogenous signaling for boosting systemic tumor immunotherapy - Jun-Long Liang; Xiao-Kang Jin; Shi-Man Zhang; Qian-Xiao Huang; Ping Ji; Xin-Chen Deng; Si-Xue Cheng; Wei-Hai Chen; Xian-Zheng Zhang (Science Bulletin, 2023)

A simulation-aided approach in examining the viability of passive daylighting techniques on inclined windows - Ya Hui Teo; Jun Hong Yap; Hui An; Nenggang Xie; Jie Chang; Simon Ching Man Yu; Wai Ching Poon; Limao Zhang; Kang Hao Cheong (Energy and Buildings, 2023)

Exploring the nonlinear partitioning mechanism of volatile organic contaminants between soil and soil vapor using machine learning - Jun Man; Maosheng Zhong; Qing Zhou; Lin Jiang; Yijun Yao (Chemosphere, 2023)

Simultaneous sludge minimization and membrane fouling mitigation in membrane bioreactors by using a microaerobic - Settling pretreatment module - Yi Zuo; Yanjun Shao; Lihua Wang; Yiyue Sun; Ying An; Lu-Man Jiang; Nan Yu; Rujie Hao; Chuanting Zhou; Jun Tao; Zhen Zhou (Journal of Environmental Management, 2023)

Occurrence and risk assessment of three chloroamide herbicides in water and soil environment in northeastern, eastern and southern China - Wei Wang; Yanli Man; Jun Xie; Zhi Zhang; Pingping Wang; Xingang Liu (Environmental Research, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Chemical constituents from the Antarctic lichen Usnea aurantiaco-atra and their chemotaxonomic significance - Kim-Hoa Phi; Jae Eun So; Ji Hee Kim; Man Hyung Koo; Jin-Hyoung Kim; Dockyu Kim; Jun Hyuck Lee; Seulah Lee; Ui Joung Youn (Biochemical Systematics and Ecology, 2023)

Critical roles of non-coding RNAs in lifecycle and biology of Marek’s disease herpesvirus - Man Teng; Zhi-Jian Zhu; Yongxiu Yao; Venugopal Nair; Gai-Ping Zhang; Jun Luo (Science China Life Sciences, 2023)

Using fly larvae to convert food waste for growing Oujiang color common carps: health risk assessment of polycyclic aromatic hydrocarbons - Meng Gao; Zhan-Biao Yang; Xiao-Xun Xu; Jun-Ren Xian; Yuan-Xiang Yang; Song Yang; Yu-Bon Man; Zhang Cheng (Environmental Science and Pollution Research, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Geomechanics model test and numerical simulation of 2G-NPR bolt support effect in an active fault tunnel - Shu-lin Ren; Man-chao He; Wei-jun Lin; Teng-wu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2022)

Recent development in biological activities and safety concerns of perillaldehyde from perilla plants: A review - Famous Erhunmwunsee; Chao Pan; Kunlong Yang; Yongxin Li; Man Liu; Jun Tian (Critical Reviews in Food Science and Nutrition, 2022)

Asymmetric Contribution of Blastomere Lineages of First Division of the Zygote to Entire Human Body Using Post-Zygotic Variants - Seong Gyu Kwon; Geon Hue Bae; June Hyug Choi; Nanda Maya Mali; Mee Sook Jun; Dong Sun Kim; Man-Hoon Han; Seongyeol Park; Young Seok Ju; Seock Hwan Choi; Ji Won Oh (Tissue Engineering and Regenerative Medicine, 2022)

High-throughput “read-on-ski” automated imaging and label-free detection system for toxicity screening of compounds using personalised human kidney organoids - Qizheng Wang; Jun Lu; Ke Fan; Yiwei Xu; Yucui Xiong; Zhiyong Sun; Man Zhai; Zhizhong Zhang; Sheng Zhang; Yan Song; Jianzhong Luo; Mingliang You; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Improved method for measuring the δ15N compound-specific amino acids: Application on mesopelagic fishes in the South China Sea - Fuqiang Wang; Ying Wu; Lin Zhang; Jie Jin; Zuozhi Chen; Jun Zhang; Wing-man Lee (Acta Oceanologica Sinica, 2022)

Antiinflammatory lanostane triterpenoids from Ganoderma lucidum - Man Hyung Koo; Hae-Jung Chae; Jun Hyuck Lee; Sung-Suk Suh; Ui Joung Youn (Natural Product Research, 2021)

LuxS-mediated quorum sensing system in Lactobacillus plantarum NMD-17 from koumiss: induction of plantaricin MX in co-cultivation with certain lactic acid bacteria - Li-Li Man; Dian-Jun Xiang (Folia Microbiologica, 2021)

Diversity of microbial community and its metabolic potential for nitrogen and sulfur cycling in sediments of Phu Quoc island, Gulf of Thailand - Ngoc Tung Quach; Hang Thuy Dam; Dinh Man Tran; Thi Hanh Nguyen Vu; Quoc Viet Nguyen; Kim Thoa Nguyen; Quang Huy Nguyen; Cao Bang Phi; Thanh Ha Le; Hoang Ha Chu; Van Thuoc Doan; Douglas J. H. Shyu; et al. (Brazilian Journal of Microbiology, 2021)

IL-10 Deficiency Aggravates Renal Inflammation, Fibrosis and Functional Failure in High-Fat Dieted Obese Mice - Dae Hwan Kim; So Young Chun; EunHye Lee; Bomi Kim; BoHyun Yoon; Haejung Gil; Man-Hoon Han; Yun-Sok Ha; Jun Nyung Lee; Tae Gyun Kwon; Bum Soo Kim; Byung Ik Jang (Tissue Engineering and Regenerative Medicine, 2021)
BACKGROUND: High-fat diet-induced obesity is one of the major cause of chronic renal failure. This obesity-related renal failure is mainly caused by inflammatory processes. However, the role of the major anti-inflammatory cytokine interleukin (IL)-10 has not been researched intensively. METHODS: To evaluate the effect of IL-10 deficiency on obesity-related renal failure, the in vivo study was carried with four animal groups; (1) Low-fat dieted C57BL/6 mice, (2) Low-fat dieted IL-10 knockout (KO) mice, (3) High‐fat dieted C57BL/6 mice and (4) High‐fat dieted IL-10 KO mice group. The analysis was carried with blood/urine chemistry, H&E, Oil-Red-O, periodic acid-Schiff and Masson’s trichrome staining immunohistochemistry and real-time PCR methods. RESULTS: At week 12, high‐fat dieted IL-10 KO mice showed 1) severe lipid accumulation in kidneys, cholesterol elevation (in total, serum kidney) and low-density lipoprotein increasion through the SCAP-SREBP2-LDLr pathway; (2) serious histopathologic alterations showing glomerulosclerosis, tubulointerstitial fibrosis and immune cell infiltration; (3) increased pro‐inflammatory cytokines and chemokines expression; (4) enhanced renal fibrosis; and (5) serious functional failure with high serum creatinine and BUN and proteinuria excretion compared to other groups. CONCLUSION: IL-10 deficiency aggravates renal inflammation, fibrosis and functional failure in high-fat dieted obese mice, thus IL-10 therapy could be applied to obesity-related chronic renal failure.

Investigating the spatial distribution of polychlorinated biphenyls in sediment in the Pearl River Delta, South China - Man-Ying Chen; Hong-Yin Liu; Xiao-Jun Luo; Bi-Xian Mai; Feng-Hui Lu (Environmental Monitoring and Assessment, 2021)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Expression of stem cell markers as useful complementary factors in the early detection of urinary bladder carcinogens by immunohistochemistry for γ-H2AX - Takanori Yamada; Takeshi Toyoda; Kohei Matsushita; Young-Man Cho; Jun-ichi Akagi; Tomomi Morikawa; Yasuko Mizuta; Kumiko Ogawa (Archives of Toxicology, 2021)

Effects of Exposure to Lead and Cadmium on Health of Inhabitants of Abandoned Metal Mine Area in Korea - Joo-Young Moon; Sang-Yong Eom; Jeong-Wook Seo; Jung-Eum Lee; Byung-Sun Choi; Heon Kim; Young-Seoub Hong; Jun Young Chang; Man-Joong Jeon; Won-Ju Park; Joon Sakong; Jung-Duck Park (Archives of Environmental Contamination and Toxicology, 2021)

Characterization of NMCR ‐2, a new non‐mobile colistin resistance enzyme: implications for an MCR ‐8 ancestor - Saif Ullah; Kai Ji; Jun Li; Yongchang Xu; Chengjian Jiang; Huimin Zhang; Man Huang; Youjun Feng (Environmental Microbiology, 2021)
Summary MCR‐4 and MCR‐8 are two recently identified members of an ongoing MCR family of colistin resistance. Although that aquatic reservoir for MCR‐4 is proposed, the origin and mechanism of MCR‐8 is poorly understood. Here we report a previously unrecognized non‐mobile colistin resistance enzyme, termed NMCR‐2, originating from the plant pathogen Kosakonia pseudosacchari . NMCR‐2 (551aa) gives 67.3% identity to MCR‐8 (565aa). NMCR‐2 is placed as a progenitor/ancestor for MCR‐8 in phylogeny of MCR members. Genetic study reveals that nmcr‐2 is comparable to mcr‐8 in the ability of producing phenotypic colistin resistance. Biochemical analyses determine that these two enzymes catalyse the transfer of PEA from the donor PE lipid substrate to the recipient lipid A molecule by a putative ‘ping‐pong’ trade‐off. Further experiment of protein engineering demonstrates that the two motifs (TM region and catalytic domain) of NMCR‐2 are functionally exchangeable with that of MCR‐8, rather than MCR‐1. Physiological impacts of nmcr‐2 and/or mcr‐8 are detected in Escherichia coli , featuring with fitness cost. Evidently, the action and mechanism of NMCR‐2 is analogous to that of MCR‐8. Therefore, our finding underlines that NMCR‐2 might be a possible progenitor of MCR‐8.

Footbinding and non-footbinding Han Chinese females in the Qing Dynasty (1644–1912 CE) Xifengbu cemetery: a skeletal and mortuary analysis - Xiaofan Sun; Xingyu Man; Xuezhu Liao; Jiyun Yang; Jun Cao; Hong Zhu; Quanchao Zhang; Qian Wang (Archaeological and Anthropological Sciences, 2021)

Effectiveness of Adding Antiplatelets to Oral Anticoagulants in Patients with Acute Ischemic Stroke with Atrial Fibrillation and Concomitant Large Artery Steno-Occlusion - Joon-Tae Kim; Ji Sung Lee; Beom Joon Kim; Jong-Moo Park; Kyusik Kang; Soo Joo Lee; Jae Guk Kim; Jae-Kwan Cha; Dae-Hyun Kim; Tai Hwan Park; Sang-Soon Park; Kyung Bok Lee; et al. (Translational Stroke Research, 2020)

A high-density genetic map and multiple environmental tests reveal novel quantitative trait loci and candidate genes for fibre quality and yield in cotton - Qishen Gu; Huifeng Ke; Zhengwen Liu; Xing Lv; Zhengwen Sun; Man Zhang; Liting Chen; Jun Yang; Yan Zhang; Liqiang Wu; Zhikun Li; Jinhua Wu; et al. (Theoretical and Applied Genetics, 2020)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Isopimarane-type diterpenoids from Croton laevigatus - Man-Yu Li; Zheng-Zhi Han; Li-Fang Liu; Xiao-Zhen Wu; Wen-Jun Huang; Kai Wang; Fan Yang; Cheng-Shan Yuan (Natural Product Research, 2020)

Numerical study of the building pressure cycling method for evaluating vapor intrusion from groundwater contamination - Yanqiu Liu; Jun Man; Yue Wang; Yuting Xiao; Wei Tang; Qiang Chen; Yijun Yao (Environmental Science and Pollution Research, 2020)

Reduced ROS ‐mediated antibiotic resistance and its reverting by glucose in Vibrio alginolyticus - Song Zhang; Man‐Jun Yang; Bo Peng; Xuan‐xian Peng; Hui Li (Environmental Microbiology, 2020)
Summary Antibiotic‐resistant Vibrio alginolyticus poses a big challenge to human health and food safety. It is urgently needed to understand the mechanisms underlying antibiotic resistance to develop effective approaches for the control. Here we explored the metabolic difference between gentamicin‐resistant V . alginolyticus (VA‐R GEN ) and gentamicin‐sensitive V . alginolyticus (VA‐S), and found that the reactive oxygen species (ROS) generation was altered. Compared with VA‐S, the ROS content in VA‐R GEN was reduced due to the decreased generation and increased breakdown of ROS. The decreased production of ROS was attributed to the decreased central carbon metabolism, which is associated with the resistance to gentamicin. As such a mechanism, we exogenously administrated VA‐R GEN with the glucose that activated the central carbon metabolism and promoted the generation of ROS, but decreased the breakdown of ROS in VA‐R GEN . The gentamicin‐mediated killing was increased with the elevation of the ROS level by a synergistic effect between gentamicin and exogenous glucose. The synergistic effect was inhibited by thiourea, a scavenger of ROS. These results reveal a reduced ROS‐mediated antibiotic resistance mechanism and its reversal by exogenous glucose.

Ectopic expression of an oat SnRK2 gene, AsSnRK2D, enhances dehydration and salinity tolerance in tobacco by modulating the expression of stress-related genes - Dian-Jun Xiang; Li-Li Man; Shuai Cao; Peng Liu; Zhi-Gang Li; Xiao-Dong Wang (Brazilian Journal of Botany, 2020)

Adaptive multi-fidelity probabilistic collocation-based Kalman filter for subsurface flow data assimilation: numerical modeling and real-world experiment - Jun Man; Qiang Zheng; Laosheng Wu; Lingzao Zeng (Stochastic Environmental Research and Risk Assessment, 2020)

Physiochemical Changes in Lipid-rich Mackerel during the Preparation of Smoked Mold Ripened Meat Products - Joon-Young Jun; Min-Jeong Jung; Jun-Seok Kum; Gwang-Woo Kim; Jae-Hyung Jung; Jae-Man Sim; In-Hak Jeong; Byoung-Mok Kim (Journal of Aquatic Food Product Technology, 2020)

Liminal presence of exo-microbes inoculating coconut endosperm waste to enhance black soldier fly larval protein and lipid - Sabrina Hasnol; Jun Wei Lim; Chung Yiin Wong; Man Kee Lam; Seteno K. O. Ntwampe (Environmental Science and Pollution Research, 2020)

Effect of probiotic administration on gut microbiota and depressive behaviors in mice - Quan Feng Liu; Hong-Man Kim; Sanghyun Lim; Myung-Jun Chung; Chi-Yeon Lim; Byung-Soo Koo; Seok-Seong Kang (DARU Journal of Pharmaceutical Sciences, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

First report of actinidia virus A and B infecting kiwifruit in Jiangxi province in China - Man Fei Zou; Ming Feng Yan; Ying Zhou; Yuan Xiu Wang; Gui Hong Xiong; Jun Xi Jiang (Journal of Plant Pathology, 2020)

Evaluating the effects of transgenic Bt rice cultivation on soil stability - Ying-ying Song; Jia-wen Liu; Li-kun Li; Man-qiang Liu; Xiao-yun Chen; Fa-jun Chen (Environmental Science and Pollution Research, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Optimizing the frequency ratio method for landslide susceptibility assessment: A case study of the Caiyuan Basin in the southeast mountainous area of China - Yi-xing Zhang; Heng-xing Lan; Lang-ping Li; Yu-ming Wu; Jun-hui Chen; Nai-man Tian (Journal of Mountain Science, 2020)

Characterization of a broad spectrum bacteriocin produced by Lactobacillus plantarum MXG-68 from Inner Mongolia traditional fermented koumiss - Li-Li Man; Dian-Jun Xiang (Folia Microbiologica, 2019)

Dual Functions of Microglia in Ischemic Stroke - Chuan Qin; Luo-Qi Zhou; Xiao-Tong Ma; Zi-Wei Hu; Sheng Yang; Man Chen; Dale B. Bosco; Long-Jun Wu; Dai-Shi Tian (Neuroscience Bulletin, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Preparation and Characterization of Human Adipose Tissue-Derived Extracellular Matrix, Growth Factors, and Stem Cells: A Concise Review - So Young Chun; Jeong Ok Lim; Eun Hye Lee; Man-Hoon Han; Yun-Sok Ha; Jun Nyung Lee; Bum Soo Kim; Min Jeong Park; MyungGu Yeo; Bongsu Jung; Tae Gyun Kwon (Tissue Engineering and Regenerative Medicine, 2019)

The novel methoxetamine analogs N-ethylnorketamine hydrochloride (NENK), 2-MeO-N-ethylketamine hydrochloride (2-MeO-NEK), and 4-MeO-N-ethylketamine hydrochloride (4-MeO-NEK) elicit rapid antidepressant effects via activation of AMPA and 5-HT2 receptors - Leandro Val Sayson; Chrislean Jun Botanas; Raly James Perez Custodio; Arvie Abiero; Mikyung Kim; Hyun Jun Lee; Hee Jin Kim; Sung Yeun Yoo; Kun Won Lee; Hye Won Ryu; Srijan Acharya; Kyeong-Man Kim; et al. (Psychopharmacology, 2019)

Contrasting Soil Bacterial and Fungal Communities between the Swamp and Upland in the Boreal Forest and their Biogeographic Distribution Patterns - Jing Li; Hang-Wei Hu; Zhang-Jie Cai; Yin-Ru Lei; Man-Yin Zhang; Wei Li; Jun-Tao Wang (Wetlands, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Simulation study of the void space gas effect on slope instability triggered by an earthquake - Zhou Zhou; Xiao-qun Wang; Yu-feng Wei; Jun-hui Shen; Man Shen (Journal of Mountain Science, 2019)

Strain Screening from Traditional Fermented Soybean Foods and Induction of Nattokinase Production in Bacillus subtilis MX-6 - Li-Li Man; Dian-Jun Xiang; Chun-Lan Zhang (Probiotics and Antimicrobial Proteins, 2019)

NaCl promotes antibiotic resistance by reducing redox states in Vibrio alginolyticus - Jun Yang; Zao‐Hai Zeng; Man‐Jun Yang; Zhi‐Xue Cheng; Xuan‐Xian Peng; Hui Li (Environmental Microbiology, 2018)
Summary The development of antibiotic resistance in Vibrio alginolyticus represents a threat to human health and fish farming. Environmental NaCl regulation of bacterial physiology is well documented, but whether the regulation contributes to antibiotic resistance remains unknown. To explore this, we compared minimum inhibitory concentration (MIC) of V. alginolyticus cultured in different media with 0.5%–10% NaCl, and found that the MIC increased as the NaCl concentration increased, especially for aminoglycoside antibiotics. Consistent with this finding, internal NaCl also increased, while intracellular gentamicin level decreased. GC–MS‐based metabolomics showed different distributions of pyruvate cycle intermediates among 0.5%, 4% and 10% NaCl. Differential activity of enzymes in the pyruvate cycle and altered expression of Na(+)‐NQR led to a reducing redox state, characterized by decreased levels of NADH, proton motive force (PMF) and ATP. Meanwhile, NaCl negatively regulated PMF as a consequence of the reducing redox state. These together are responsible for the decreased intracellular gentamicin level with the increased external level of NaCl. Our study reveals a previously unknown redox state‐dependent mechanism regulated by NaCl in V. alginolyticus that impacts antibiotic resistance.

Full Thickness Skin Expansion ex vivo in a Newly Developed Reactor and Evaluation of Auto-Grafting Efficiency of the Expanded Skin Using Yucatan Pig Model - Man-Il Huh; Soo-Jin Yi; Kyung-Pil Lee; Hong Kyun Kim; Sang-Hyun An; Dan-Bi Kim; Rae-Hyung Ryu; Jun-Sik Kim; Jeong Ok Lim (Tissue Engineering and Regenerative Medicine, 2018)

Cellular stress and redox activity proteins are involved in gastric carcinogenesis associated with Helicobacter pylori infection expressing high levels of thioredoxin-1 - Yan-yan Shi; Jing Zhang; Ting Zhang; Man Zhou; Ye Wang; He-jun Zhang; Shi-gang Ding (Journal of Zhejiang University-SCIENCE B, 2018)

First report of leaf spot caused by Pseudocercospora puerariicola on kudzu (Pueraria lobata) in Jiangxi China - Ming Feng Yan; Man Fei Zou; Bing Liu; Yuan Xiu Wang; Gui Hong Xiong; Jun Xi Jiang (Journal of Plant Pathology, 2018)

Molecular cloning of adipose triglyceride lipase (ATGL) gene from blunt snout bream and its expression after LPS-induced TNF-α factor - Yong-Jun Dai; Wen-Bin Liu; Xiang-Fei Li; Man Zhou; Chao Xu; Yu Qian; Guang-Zhen Jiang (Fish Physiology and Biochemistry, 2018)

A new Em-like protein from Lactuca sativa, LsEm1, enhances drought and salt stress tolerance in Escherichia coli and rice - Dian-Jun Xiang; Li-Li Man; Chun-Lan Zhang; Peng-Liu; Zhi-Gang Li; Gen-Chang Zheng (Protoplasma, 2018)

Estimation of the joint roughness coefficient (JRC) of rock joints by vector similarity measures - Rui Yong; Jun Ye; Qi-Feng Liang; Man Huang; Shi-Gui Du (Bulletin of Engineering Geology and the Environment, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Surface IgM λ light chain is involved in the binding and infection of infectious bursal disease virus (IBDV) to DT40 cells - Jiaqi Chi; Leiming You; Peipei Li; Man Teng; Gaiping Zhang; Jun Luo; Aiping Wang (Virus Genes, 2018)

Characteristics of polycyclic aromatic hydrocarbons in PM2.5 emitted from different cooking activities in China - Yun-Chun Li; Jia-Qian Qiu; Man Shu; Steven Sai Hang Ho; Jun-Ji Cao; Ge-Hui Wang; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2018)

Salidroside improved cerebrovascular vasodilation in streptozotocin-induced diabetic rats through restoring the function of BKCa channel in smooth muscle cells - Yu-Guang Ma; Jun-Wei Wang; Yin-Bin Zhang; Bao-Feng Wang; Zhi-Jun Dai; Man-Jiang Xie; Hua-Feng Kang (Cell and Tissue Research, 2017)

Prostanoid EP3 receptor agonist sulprostone enhances pacemaker activity of colonic interstitial cells of Cajal - Man Woo Kim; Han Yi Jiao; Seok Won Kim; Chan Guk Park; Mei Jin Wu; Chansik Hong; Seok Choi; Jae Yeoul Jun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Evapotranspiration versus oxygen intrusion: which is the main force in alleviating bioclogging of vertical-flow constructed wetlands during a resting operation? - Guofen Hua; Qiuwen Chen; Jun Kong; Man Li (Environmental Science and Pollution Research, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Frequency characteristics and far-field effect of gravity perturbation before earthquake - Jian-Ke Qiang; Kai Lu; Qian-Jiang Zhang; Kai-Feng Man; Jun-Ying Li; Xian-Cheng Mao; Jian-Qing Lai (Applied Geophysics, 2017)

Over-Expression of PmHSP17.9 in Transgenic Arabidopsis thaliana Confers Thermotolerance - Xue-Li Wan; Jie Yang; Xiao-Bai Li; Qiao Zhou; Cong Guo; Man-Zhu Bao; Jun-Wei Zhang (Plant Molecular Biology Reporter, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Morphology and phylogenetic position of a freshwater Prasiola species (Prasiolales, Chlorophyta) in Korea - Moon Sook Kim; Man-Sig Jun; Cho A Kim; Jihae Yoon; Jin Hee Kim; Ga Youn Cho (Algae, 2015)

Expression of a scorpion toxin gene BmKit enhances the virulence of Lecanicillium lecanii against aphids - Ming Xie; Yan-Jun Zhang; Xiao-Man Zhai; Jin-Jin Zhao; De-Liang Peng; Gang Wu (Journal of Pest Science, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Molecular characterization and expression analysis of a novel dual-CRD C-type lectin in kuruma shrimp (Marsupenaeus japonicus) - Man Zhang; Yong Mao; Jun Wang; Wenrong Feng; Xiaohong Song; Yongquan Su (Acta Oceanologica Sinica, 2015)

Quinoxaline-2,3-diones: potential d-amino acid oxidase (DAAO) inhibitors - Dongsheng Xie; Yanchao Wang; Jin Xie; Jun Lu; Junjun Cui; Man Zhang; Lei Fu; Yongxiang Wang (Medicinal Chemistry Research, 2014)

Isolated Frontal Sinusitis Treated Using an Anterior-to-Ethmoidal Bulla Surgical Approach - Jun-feng Ji; You Cheng; Tian-you Wang; Kun-min Wu; Man-jie Jiang; Wei Cheng; Zhi-yi Wang; Fei Xue; Yong Zhang; Qiu-ping Wang (Cell Biochemistry and Biophysics, 2014)

Repair of Ear Cartilage Defects with Allogenic Bone Marrow Mesenchymal Stem Cells in Rabbits - You Cheng; Peng Cheng; Fei Xue; Kun-min Wu; Man-jie Jiang; Jun-feng Ji; Chun-hua Hang; Qiu-ping Wang (Cell Biochemistry and Biophysics, 2014)

Phytostabilization and Physicochemical Responses of Korean Ecotype Solanum nigrum L. to Cadmium Contamination - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Sung-Jun Hong; Muhammad Waqas; Gun-Seok Park; Yunyoung Kwak; JungBae Choi; Byung-Kwon Jung; Man Park; In-Jung Lee; Jae-Ho Shin (Water, Air, & Soil Pollution, 2014)

Effects of a hemagglutinin D222G substitution on the pathogenicity of 2009 influenza A (H1N1) virus in mice - Jin Il Kim; Ilseob Lee; Sehee Park; Sangmoo Lee; Min-Woong Hwang; Joon-Yong Bae; Jun Heo; Donghwan Kim; Seok-Il Jang; Jin-Won Song; Man-Seong Park (Archives of Virology, 2014)

Scoring the collective effects of SNPs: association of minor alleles with complex traits in model organisms - DeJian Yuan; ZuoBin Zhu; XiaoHua Tan; Jie Liang; Chen Zeng; JieGen Zhang; Jun Chen; Long Ma; Ayca Dogan; Gudrun Brockmann; Oliver Goldmann; Eva Medina; et al. (Science China Life Sciences, 2014)

감마선 조사에 의한 헤파린이 도입된 박테리아 셀룰로오스의 골조 직공학용 지지체로서의 개발 및 특성분석 - Sung In Jeong; Jin-Oh Jeong; Jong-Bae Choi; Young Min Shin; Jong-Seok Park; Hui-Jeong Gwon; Young-Chang Nho; Sung-Jun An; Man-Young Park; Youn-Mook Lim (Tissue Engineering and Regenerative Medicine, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Coumarin-containing aminophosphonates bridged with chiral side chain: synthesis and influence of chirality on cytotoxicity and DNA binding - Ya-Jun Li; Man-Yi Ye; Ri-Zhen Huang; Gui-Yang Yao; Ying-Ming Pan; Zhi-Xin Liao; Heng-Shan Wang (Medicinal Chemistry Research, 2014)

Calibration of the Normal Cutoff Values of Systolic Dyssynchrony of the Left Ventricular Synchronicity in Normal Subjects Using Real-Time 3-Dimensional Echocardiography and the Effects of Age and Heart Rate - Chun-Yan Ma; Shuang Liu; Qing Zhang; Jun Yang; Li Tang; Gabriel Yip; Cheuk-Man Yu (Cell Biochemistry and Biophysics, 2014)

Catastrophe theory to assess water security and adaptation strategy in the context of environmental change - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Xia Xing-hui; He Rui-min; Shang Man-ting (Mitigation and Adaptation Strategies for Global Change, 2014)

Multi-mode PolInSAR experiments using an airborne X-band SAR system in China - Li-Jun Lu; Ji-Xian Zhang; Fen-Fen Hua; Guo-Man Huang (International Journal of Remote Sensing, 2014)

Prognostic significance of microRNA-141 expression and its tumor suppressor function in human pancreatic ductal adenocarcinoma - Zi-Man Zhu; Yue-Fang Xu; Qin-Jun Su; Jun-Dong Du; Xiang-Long Tan; Yu-Liang Tu; Jing-Wang Tan; Hua-Bao Jiao (Molecular and Cellular Biochemistry, 2014)

Passive Movement Improves the Learning and Memory Function of Rats with Cerebral Infarction by Inhibiting Neuron Cell Apoptosis - Man Li; Jun Peng; Meng-Die Wang; Yan-Ling Song; Yuan-Wu Mei; Yuan Fang (Molecular Neurobiology, 2014)

Arsenic concentration in rice, fish, meat and vegetables in Cambodia: a preliminary risk assessment - Hong-Sheng Wang; Suthipong Sthiannopkao; Zhuo-Jia Chen; Yu-Bon Man; Jun Du; Guang-Hua Xing; Kyoung-Woong Kim; Mohamed Salleh Mohamed Yasin; Jamal Hisham Hashim; Ming-Hung Wong (Environmental Geochemistry and Health, 2013)

Up-regulating Blood Brain Barrier Permeability of Nanoparticles via Multivalent Effect - Xihui Gao; Jun Qian; Shuyan Zheng; Ying Xiong; Jiahao Man; Binxin Cao; Lu Wang; Shenghong Ju; Cong Li (Pharmaceutical Research, 2013)

Molecular characteristics and evolutionary analysis of field Marek’s disease virus prevalent in vaccinated chicken flocks in recent years in China - Zu-Hua Yu; Man Teng; Jun Luo; Xin-Wei Wang; Ke Ding; Le-Le Yu; Jing-Wei Su; Jia-Qi Chi; Pu Zhao; Bo Hu; Gai-Ping Zhang; Ju-Xiong Liu (Virus Genes, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Expression of c-Src and phospho-Src in epithelial ovarian carcinoma - Yong-Wen Huang; Chen Chen; Man-Man Xu; Jun-Dong Li; Juan Xiao; Xiao-Feng Zhu (Molecular and Cellular Biochemistry, 2013)

Debris flows introduced in landslide deposits under rainfall conditions: The case of Wenjiagou gully - Jia-wen Zhou; Peng Cui; Xing-guo Yang; Zhi-man Su; Xiao-jun Guo (Journal of Mountain Science, 2013)

Molecular characterization of Japanese encephalitis viruses circulating in pigs and mosquitoes on pig farms in the Chinese province of Henan - Man Teng; Jun Luo; Jian-Ming Fan; Lu Chen; Xing-Tao Wang; Wu Yao; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2013)

The unsulfated extracellular N-terminus of vGPCR reduces the tumorigenicity of hGRO-α in nude mice - Hui Wu; YongMing Fu; Jun Xiao; Man Zhou; Wei Zhou; Hao Feng (Science China Life Sciences, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Nitric oxide acts as a signal molecule in microwave pretreatment induced cadmium tolerance in wheat seedlings - Zong-Bo Qiu; Jun-Li Guo; Man-Man Zhang; Meng-Yun Lei; Zhen-Lin Li (Acta Physiologiae Plantarum, 2013)

Efficacy of endosulfan and fipronil and joint toxic action of endosulfan mixtures against Leptinotarsa decemlineata (Say) - Xiao-qin Shi; Man-Hui Xiong; Wei-Hua Jiang; Zhi-Tian Wang; Wen-Chao Guo; Zhen-Han Xia; Wen-Jun Fu; Guo-Qing Li (Journal of Pest Science, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Common polymorphisms (rs2241766 and rs1501299) in the ADIPOQ gene are not associated with hypertension susceptibility among the Chinese - Bo Xi; Dan He; Qijuan Wang; Jian Xue; Man Liu; Jun Li (Molecular Biology Reports, 2012)

Chromium, Selenium, and Zinc Multimineral Enriched Yeast Supplementation Ameliorates Diabetes Symptom in Streptozocin-Induced Mice - Jun Liu; Wei Bao; Man Jiang; Yan Zhang; Xiping Zhang; Liegang Liu (Biological Trace Element Research, 2012)

Nacre-driven water-soluble factors promote wound healing of the deep burn porcine skin by recovering angiogenesis and fibroblast function - Kyunghee Lee; Hyunsoo Kim; Jin Man Kim; Yeoun Ho Chung; Tae Yoon Lee; Hyun-Sook Lim; Ji-Hye Lim; Taewoon Kim; Jin Seung Bae; Chang-Hoon Woo; Keuk-Jun Kim; Daewon Jeong (Molecular Biology Reports, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Biosafety evaluation of bacteriophages for treatment of diarrhea due to intestinal pathogen Escherichia coli 3-2 infection of chickens - Hao Li; Man-Li Ma; Hui-Jun Xie; Jian Kong (World Journal of Microbiology and Biotechnology, 2012)

Phellinus baumii ethyl acetate extract inhibits lipopolysaccharide-induced iNOS, COX-2, and proinflammatory cytokine expression in RAW264.7 cells - Taddesse Yayeh; Won Jun Oh; Seung-Choon Park; Tae-Hwan Kim; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Sang-Keun Kim; Seung-Bok Hong; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2012)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Major Pollutants in Soils of Abandoned Agricultural Land Contaminated by e-Waste Activities in Hong Kong - Brenda Natalia Lopez; Yu Bon Man; Yin Ge Zhao; Jin Shu Zheng; Anna Oi Wah Leung; Jun Yao; Ming Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

A strategy to deal with water crisis under climate change for mainstream in the middle reaches of Yellow River - Xiao-jun Wang; Jian-yun Zhang; Rui-min He; ElMahdi Amgad; ElSawah Sondoss; Man-ting Shang (Mitigation and Adaptation Strategies for Global Change, 2011)

Fine mapping and candidate gene analysis of ptgms2-1, the photoperiod-thermo-sensitive genic male sterile gene in rice (Oryza sativa L.) - Jianjun Xu; Baohe Wang; Yinhui Wu; Peina Du; Jun Wang; Man Wang; Chuandeng Yi; Minghong Gu; Guohua Liang (Theoretical and Applied Genetics, 2011)

Molecular Identification and Physiological Characterization of a Putative Novel Plasma Membrane Protein from Arabidopsis Involved in Glucose Response - Moon-Soo Chung; Ping Huang; Chan Man Ha; Ji Hyung Jun; Sung-Ju Ahn; Fu-chun Zhang; Hyun-Jong Bae; Baik Ho Cho; Cheol Soo Kim (Journal of Plant Biology, 2011)

Metalloporphyrin intercalation in liposome membranes: ESR study - Dariusz Man; Rudolf Słota; Małgorzata A. Broda; Giuseppe Mele; Jun Li (JBIC Journal of Biological Inorganic Chemistry, 2011)

Erratum to: Marek’s disease virus-encoded microRNAs: genomics, expression and function - Jun Luo; Man Teng; JianMing Fan; FangYu Wang; Ling Zhou; RuiGuang Deng; GaiPing Zhang (Science China Life Sciences, 2010)

Marek’s disease virus-encoded microRNAs: genomics, expression and function - Jun Luo; Man Teng; JianMing Fan; FangYu Wang; Ling Zhou; RuiGuang Deng; GaiPing Zhang (Science China Life Sciences, 2010)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Coexpression and characterization of the human large-conductance Ca2+-activated K+ channel α + β1 subunits in HEK293 cells - Jun Li; Chang-Lei Deng; Fang Gao; Jiu-Hua Cheng; Zhi-Bin Yu; Li Liu; Man-Jiang Xie (Molecular and Cellular Biochemistry, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Influence of ginsenoside Rg1, a panaxatriol saponin from Panax notoginseng, on renal fibrosis in rats with unilateral ureteral obstruction - Xi-sheng Xie; Man Yang; Heng-cuang Liu; Chuan Zuo; Zi Li; Yao Deng; Jun-ming Fan (Journal of Zhejiang University-SCIENCE B, 2008)

Numerical investigation and identification of susceptible sites of atherosclerotic lesion formation in a complete coronary artery bypass model - Jun-Mei Zhang; Leok Poh Chua; Dhanjoo N. Ghista; Simon Ching Man Yu; Yong Seng Tan (Medical & Biological Engineering & Computing, 2008)

Genetic relatedness and genetic diversity of ornamental mei (Prunus mume Sieb. et Zucc.) as analysed by AFLP markers - Chao-Dong Yang; Jun-Wei Zhang; Xiao-Lan Yan; Man-Zhu Bao (Tree Genetics & Genomes, 2008)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

Inhibition of pacemaker currents by nitric oxide via activation of ATP-sensitive K+ channels in cultured interstitial cells of Cajal from the mouse small intestine - Chan Guk Park; Young Dae Kim; Man Yoo Kim; Jun Soo Kim; Seok Choi; Cheol Ho Yeum; Shankar Prasad Parajuli; Jong Seong Park; Han Seong Jeong; Insuk So; Ki Whan Kim; Jae Yeoul Jun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Cloning and Characterization of a Second form of the Rice Adenine Phosphoribosyl Transferase Gene (OsAPT2) and its Association with TGMS - Chun-Jiang Zhou; Jun Li; Ji-Cheng Zou; Feng-Shan Liang; Chun-Jiang Ye; De-Min Jin; Man-Li Weng; Bin Wang (Plant Molecular Biology, 2006)

Production, purification, and characterization of a novel thermostable serine protease from soil isolate, Streptomyces tendae - Chi-Nam Seong; Jung-Sun Jo; Sang-Ki Choi; Si-Wouk Kim; Sung-Jun Kim; Oh-Hyung Lee; Ji-Man Han; Jin-Cheol Yoo (Biotechnology Letters, 2004)

Cloning, Expression, and Biological Function of a dTDP-Deoxyglucose Epimerase (gerF) Gene from Streptomyces sp. GERI-155 - Jae-Kyung Sohng; Hyung-jun Kim; Doo-Hyun Nam; Dong-Ok Lim; Ji-Man Han; Hyo-Jung Lee; Jin-Cheol Yoo (Biotechnology Letters, 2004)

Evaluation of Precipitation Composition at an Urban and a Rural Area for the Central Korean Peninsula - Man-Goo Kim; Mi-Hee Kang; Ki-Jun Park; Bo-Kyung Lee; Dong-Soo Lee (Water, Air, & Soil Pollution, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Gene gun-mediated in vivo analysis of tissue-specific repression of gene transcription driven by the chicken ovalbumin promoter in the liver and oviduct of laying Hens - Tatsuo Muramatsu; Takashi Imai; Hyi-Man Park; Hisako Watanabe; Akihiro Nakamura; Jun-ichi Okumura (Molecular and Cellular Biochemistry, 1998)